Zeugnisse des Okkulten: Literatur und Esoterik im Wiener Fin de Siècle - Kaufmann, Kira (Brill, 2025)
The research project aims to make the occult visible as a component of Viennese modernism. It connects to a research context that understands occultism and esotericism not as opposed to modernism, but rather as concepts of knowledge that promoted it. Unlike Berlin, Munich and Leipzig, Vienna around 1900 has been little researched in this context to date. This study remedies this research gap by examining an extensive and disparate corpus of texts in detail for the first time. Das Forschungsprojekt verfolgt das Ziel, das Okkulte als Bestandteil der Wiener Moderne sichtbar zu machen. Es schließt an einen Forschungskontext an, der Okkultismus und Esoterik nicht als der Moderne entgegengesetzte, sondern vielmehr als sie befördernde Wissenskonzepte begreift. Die vorliegende Studie behebt diese Forschungslücke, indem sie erstmals ein umfangreiches und disparates Textkorpus eingehend in den Blick nimmt.